Public enterprises in the national economy (New Delhi, 1976)
This volume contains a resume of the deliberations and a statement of Conclusions of the first National Convention of public Enterprises- 1976, organised in April this year by the standing conference of public Enterprises in collaboration with the Bureau of Public Enterprises. The Prime Minister Smt. Indira Gandhi wa so kind as to inaugurate the National Convention. Her presence with us gave all of us a great deal of inspiration and encouragement and it need hardly be said that her association with the National Convention gave the event a great dignity and prestige.
Keywords: Public enterprises